2019
DOI: 10.1108/tqm-02-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of UTAUT and e-service quality in internet banking adoption setting

Abstract: Purpose Technology adoption is a great challenge in the banking sector of Pakistan. A recent report issued by state bank of Pakistan revealed that there is a squeak growth, only 3 percent, in internet banking adoption. In order to effectively delve into the issue of internet banking adoption, the purpose of this paper is to use unified theory of acceptance and use of technology factors, namely performance expectancy and effort expectancy and e-service quality (E-SQ), as theoretical lens for this study. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 53 publications
(72 reference statements)
5
44
0
1
Order By: Relevance
“…The finding showed that behavioural intention significantly mediated the variance changes in relationship between performance expectancy and use behaviour of Nigerian lecturers on podcast. This finding is consistent with Rahi and Abd. Ghani (2019) finding that suggested performance expectancy as a significant mediator of the relationship between effort expectancy and intention to use technology.…”
Section: Performance Expectancy and Use Behavioursupporting
confidence: 93%
See 1 more Smart Citation
“…The finding showed that behavioural intention significantly mediated the variance changes in relationship between performance expectancy and use behaviour of Nigerian lecturers on podcast. This finding is consistent with Rahi and Abd. Ghani (2019) finding that suggested performance expectancy as a significant mediator of the relationship between effort expectancy and intention to use technology.…”
Section: Performance Expectancy and Use Behavioursupporting
confidence: 93%
“…This finding is consistent with Rahi and Abd. Ghani ( 2019 ) finding that suggested performance expectancy as a significant mediator of the relationship between effort expectancy and intention to use technology. Binnawas et al ( 2019 ) study considered behavioural intention as dependent variable.…”
Section: Discussionmentioning
confidence: 99%
“…Other than mobile applications, the UTAUT model is also used in explaining behavioral intention to use technology in other various fields, such as the use of big data techniques in service companies [51]; adopt self-service parcel services for last-mile delivery [52]; urban delivery drivers' intention to adopt electric trucks [52]; internet banking adoption [53,54,55], user acceptance and use of open government data (OGD) / egovernment [56,57,58,59,60] intention to use an enterprise resource planning (ERP) system [61,62], intention to use Airline Companies' e-services [63]; acceptance of automated road transport systems (ARTS) [64]; intention to adopt technology in medical or health field [65,66,67,68,69,24] adoption of online tax filing [70]; adoption of e-book [71,73] decision to use automated public transport [73]; and rural households' renewable energy usage intention [74].…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…In order to confirm lateral collinearity of the constructs the criterion is that the inner variance inflation factor should be less than 3.3 as suggested by Samar Rahi and Abd. Ghani (2019b). Findings of the analysis showed that all VIF values are lower than 3.3 indicated that this study is free from multicollinearity issues and adequate for further analysis.…”
Section: Structural Modelmentioning
confidence: 77%